2022
DOI: 10.1155/2022/9579766
|View full text |Cite
|
Sign up to set email alerts
|

Applying Activity System-Based Process Model in Augmented Reality-Based Learning for Natural Science Course in Elementary School

Abstract: Since learning environments have the support of innovational technology, blended learning environments could integrate the physical learning methods with multimedia learning materials, which combines the use of technology with the traditional teaching methods and offers a potential for teachers and students to meet the requirements of learning flexibility and innovation. This study aims to redesign a user-centered Activity System-Based Process Model (ASPM) and integrate the Augmented Reality (AR) into blended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The ability of augmented reality to effectively enrich natural sciences and their branches emerged. In a study involving 109 primary education students (experimental group: 57 students and control group: 52 students), Huang et al (2022) explored the use of augmented reality as a means to support natural science courses. The outcomes of the study indicated that students that learned through the use of the augmented reality application demonstrated a more positive attitude toward natural sciences and achieved better academic performance.…”
Section: Augmented Reality In Natural Sciences Educationmentioning
confidence: 99%
“…The ability of augmented reality to effectively enrich natural sciences and their branches emerged. In a study involving 109 primary education students (experimental group: 57 students and control group: 52 students), Huang et al (2022) explored the use of augmented reality as a means to support natural science courses. The outcomes of the study indicated that students that learned through the use of the augmented reality application demonstrated a more positive attitude toward natural sciences and achieved better academic performance.…”
Section: Augmented Reality In Natural Sciences Educationmentioning
confidence: 99%
“…Another study by Huang, Chou, Chen, and Tsai (2022) evaluated the effects of augmented reality on students' learning outcomes using an Activity System-Based Process Model in an elementary school natural science class. Students in a Taiwanese elementary school's fourth grade made up the participants.…”
Section: Review Of Past Literaturementioning
confidence: 99%
“…Likewise, through a research developed in Taiwan, the feasibility of AR for learning content, internal components of a computer, focused on the processes of motivation, understanding, learning and thinking in the construction of new knowledge was demonstrated [23].…”
Section: Introductionmentioning
confidence: 99%